Energy absorption and optimization of Bi-directional corrugated honeycomb aluminum. (15th August 2021) - Xing, Youdong; Yang, Siyi; Lu, Shiqing; An, Yukun; Zhao, Ertuan; Zhai, John
Abstract: To replace wood as the filler material for the impact limiter of the spent nuclear fuel transportation cask, a bi-directional corrugated honeycomb aluminum (BDCHA) was manufactured. First, five materials with different cell thickness/cell size ratios ( t 0 /a ) were designed, and compression tests were performed under quasi-static conditions. The results show that the initial peak stress and the plateau stress both increase with the increase of the t 0 /a ratio. The plateau zone determines the energy absorption performance; therefore, this study focuses on the analysis of the mechanical properties of the plateau stage. Furthermore, through the compression theory, the energy dissipation process of the unit cell was evaluated, and the mean stress equation was obtained; the theoretically obtained plateau stress was similar to the test plateau stress. Moreover, the ideal constitutive relationship of the material based on the t 0 /a ratio under static load was derived. Finite element analysis was used for simulation. The stress-strain results of the test and the simulation were close. Furthermore, the structural parameters were optimized via multiobjective optimization. Through the analysis of the mechanical properties of BDCHA, derived its rationality and feasibility as a shock-absorbing filling material.